The Relationship between Premenstrual Syndrome and Women's Marital Satisfaction - Zohreh Karimiankakolaki; Seyed Saeed Mazloomy Mahmoodabad; Fatemeh Heidari; Sakineh Gerayllo; Farahnaz Khabiri (Mashhad University of Medical Sciences, 2019)
Background & aim: Premenstrual Syndrome (PMS) includes different symptoms that appear periodically throughout the luteal phase of the menstrual period. The PMS has not been properly investigated as an influencing factor of marital satisfaction. Thus the purpose of this study was to assess the relationship between PMS and its symptoms with women's marital satisfaction. Methods: This cross-sectional study was conducted on 246 women referred to health centers in Yazd, Iran. The data were collected through the Index of Marital Satisfaction and Premenstrual Syndrome Screening Tool and analyzed in SPSS software (version 18) using the Chi-Square test. Results: According to the results, "somatic symptom disorders, such as breast pain, headache, muscle pain, arthritis, bloating, and weight gain" (%22.8) and "anger and irritability" (%21.5) obtained the highest frequency in terms of syndrome severity. With regard to the effect of symptoms on daily life, the strongest impact was on "the relationship with the family" (%10.6). The results showed that the levels of marital dissatisfaction among women with PMS (P=0.013) were higher, compared to the non-affected population. Conclusion: The severe symptoms of this syndrome disrupt family relationship leading to marital dissatisfaction. Therefore, the women and their families are required to receive the required training for better communication in this period.